Management of cocoa: constraints during acquisition and application of pesticides in the humid forest zones of Southern Cameroon - Sonwa, D.J.; Coulibaly, O.; Weise, Stephan F.; Adesina, A.A.; Janssens, M. (Elsevier, 2008)
Subsidies for inputs, such as pesticides, enabled about 400 000 households in southern Cameroon to grow cocoa and provide for basic needs such as food, education, bride price and house construction. Economic liberalization resulted in disengagement of the State in favor of the private sector and engendered a new behavior pattern among cocoa farmers. This study focuses on the constraints inherent in the acquisition and application of pesticides for cocoa growing on small farms in the tropical rainforest areas of southern Cameroon. Over 50% of farmers use chemical pesticides, but the high cost and lack of availability in rural areas are cited, respectively by 65% and 55% of cocoa farmers as major constraints by users of pesticides. Only 21% of cocoa farmers buy their pesticides in the village. Fungicides are the main pesticide used to control Phytophthora megakarya, but farmers do not apply the recommended application rate so production is low. Some farmers form groups to circumvent production problems, while some use plant extracts. To increase production it is essential to improve safe practices in the purchase, transportation; storage, handling and application of pesticides and promote integrated pest management in southern Cameroon.